2014
DOI: 10.1007/s13277-014-1932-y
|View full text |Cite
|
Sign up to set email alerts
|

High serum transforming growth factor beta 1 (TGFB1) level predicts better survival in breast cancer

Abstract: The transforming growth factor beta 1 (TGFB1) is a regulatory cytokine with both tumor suppressor and tumor-promoting effects in breast cancer (BC) cell lines and tissue. Data about level of circulating TGFB1 and its prognostic significance in BC patients is conflicting. The objective of this study is to determine the clinical significance of the serum TGFB1 levels in BC patients. We enrolled 96 female patients with histopathologically diagnosed BC who did not receive chemotherapy (CT) or radiotherapy. Serum T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In breast cancer patients, mRNA levels of TGF-b, IL-10 and Foxp3 were significantly higher than in healthy controls, which was consistent with previous studies (7,15,49,50). We also found that mRNA levels of IL-10 were higher in stage IV breast cancer patients, with a strong trend, but there was no correlation between other tumor characteristics, possibly because of the limited number of patients.…”
Section: Discussionsupporting
confidence: 91%
“…In breast cancer patients, mRNA levels of TGF-b, IL-10 and Foxp3 were significantly higher than in healthy controls, which was consistent with previous studies (7,15,49,50). We also found that mRNA levels of IL-10 were higher in stage IV breast cancer patients, with a strong trend, but there was no correlation between other tumor characteristics, possibly because of the limited number of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Prognostic impact of plasma levels is therefore controversial [3438]. In this patient cohort we observed a significant negative correlation of pre-therapeutic TGFβ1 with overall survival.…”
Section: Discussionmentioning
confidence: 80%
“…ICAM-1 is a transmembrane glycoprotein in the immunoglobulin superfamily, which participates in oral cancer progression and induces macrophage/SCC-cell adhesion [ 13 ]. Ciftci et al [ 14 ] indicated that serum TGFB1 level might be elevated in breast cancer patients and had a favorable prognostic value. CDH1, involved in cell adhesion, can code the adhesion protein E-cadherin that plays a central part in the process of epithelial morphogenesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%